Proposal for MSW management facilities location in a state of Brazil - Colvero, D.A.; Gomes, A.P.D.; Tarelho, L.A.C.; Matos, M.A.A.; Santos, K.A. (WASTES - Solutions, Treatments and Opportunities II, 2018)
The municipalities of the Goiás State, Brazil, have difficulties in the management of their Municipal Solid Waste (MSW). For instance of 20 municipalities in the micro-region of the Federal District Surroundings (FDS) only two dispose their MSW in licensed landfills. Considering this situation, the goal of this study was to propose host municipalities for the ins-tallation of shared MSW Management Facilities (MSWMF) in the micro-region of the FDS. In order to identify restriction-free areas for MSW treatment facilities location, a geographic information system was used. Subsequently, through the Center of Mass (CM) methodology, host municipalities for MSWMF were obtained. Results show that the FDS micro-region about 40% of its area which is suitable for MSW treatment facilities installation. From the CM, five MSWMF are proposed for the FDS: two municipalities with separate facilities, and the other three to be shared. The municipalities of the Goias State, Brazil, have difficulties in the management of their Municipal Solid Waste (MSW). For instance of 20 municipalities in the micro-region of the Federal District Surroundings (FDS) only two dispose their MSW in licensed landfills. Considering this situation, the goal of this study was to propose host municipalities for the installation of shared MSW Management Facilities (MSWMF) in the micro-region of the FDS. The FDS micro-region has about 40" of its area either free or subject to restrictions for location of municipal waste treatment facilities. This means that the locations for the FDS MSWMF should be well planned. Especially in municipalities which do not have free areas, such as Aguas Lindas de Goias, Novo Gama and Valparaiso de Goias. Thus, five host municipalities of MSWMF were established for the FDS micro-region.